Kajian Drug Related Problems pada Pasien Diabetes Melitus Tipe 2 yang Terinfeksi Covid-19 - Pande Made Desy Ratnasari (Fakultas Farmasi Universitas Setia Budi, 2024)
Type 2 Diabetes Mellitus (T2DM) is one of several factors exacerbating Covid-19. Previous studies showed that polypharmacy might lead to Drug Related Problems (DRPs) due to some drugs administered during the management of both conditions. This study aimed to analyze DRPs in T2DM patients with Covid-19 at a private hospital in Denpasar, Bali. This study was designed as cross-sectional research in June-July 2022. Data was collected from patient medical records based on inclusion and exclusion criteria. The inclusion criteria were patients T2DM with Covid-19, aged ³18 years, hospitalized between July 2020-July 2021, received Covid-19 and antidiabetic therapy. Patients who transferred to other hospitals during treatment were excluded. The DRPs included 6 aspects, namely indications without therapy, therapy without indications, inappropriate drugs, insufficient drug doses, high drug doses, and drug interactions which were analyzed by reffering to therapeutic guidelines. Majority of 106 respondents is male (66.98%), aged 46-65 years (70.75%), had a fever (30.72%), oxygen saturation 91-95% (55.66%), blood glucose 228.38 mg/dL, temperature 36.68°C, degree of high severity (49.06%), length of stay ≥10 days (52.83%), and final status as discharge (80.19%). Patients received an average of 10.89±3.46 number of drugs. The highest number of antidiabetic use was rapid-acting insulin group (38.97%) then insulin aspart (20.00%). A number of 86.00% of the prescribed patients had experienced at least 1 type of DRPs (61.54%). The top three DRPs events found in this study were drug interactions (87,75%), inappropriate drugs (7,28%), and therapy without indications (4,97%). Role of pharmacists is required for preventing and minimizing DRPs events in the practice.